An analysis on the river water quality- climate change effect phenomena in Tuaran River, Sabah, Malaysia - Abdullah, Mohd Harun; Park, Ji Hyung; Aris, Ahmad Zaharin; Praveena, Sarva Mangala (2009)
Changes in rainfall directly affect water resources management, hydrology, agriculture and ecosystems. Therefore, it is important to investigate the changes in the spatial rainfall pattern in order to assess the implication on climate and water quality changes. A total of 8-years (1990-1997) temperature, annual rainfall, suspended solids and discharge data of Tuaran River were analysed to assess climate and water quality changes. The key idea of this paper is to reveal the trends in rainfall pattern with water quality. The temperature and annual rainfall series were calculated for descriptive statistics using annual rainfall data (1990-1997) to show the impacts of climate change. An annual rainfall data were related with suspended solids and discharge recorded from 1990 to 1997 to cater a general estimation regarding rainfall patterns changes which directly affect the water quality. Output of the study revealed that even though the climate change impact on water quality of Tuaran river, it seems not to be a serious problem of total studied years (1990-1997). This study recommends continuous water quality monitoring and meteorological data should be collected for a long period to assess the trends in rainfall pattern with water quality. This enables more understanding on the impact of climate changes to the rainfall pattern and water quality.